Kutub Al-Lughah Al-Arabiyyah Al-Muqarrarah Li Thalabah Al-Madrasah Al-Mutawassithah Al-Islamiyyah: Dirasah Tanqihiyah Min Haitsu Al-Mawad Wa At-Taqdim - Afif Amrullah; Maslathif Dwi Purnomo (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2022)
This research addresses the existing problems around the materials of the Arabic language textbooks entitled "Bahasa Arab" issued by the Ministry of Religious Affairs and their relationship to the context of teaching and learning Arabic as a foreign language for students in Indonesia. While the focus of this research is on the texts of textbooks for seventh, eighth and ninth grade students in the Junior Islamic high school on the 2013 curriculum, then the type of this research belongs to the category of library researches. As for the data analysis technique, the researcher followed the content analysis technique, and because the data produced by this research are qualitative data, this research was classified in an analytical and descriptive scheme. After completing the process of identifying and analyzing the data, the result showed that the textbooks for students in the Junior Islamic high school met “very good” from some of the established criteria, including: 1) the suitability of the subjects; 2) material presentation techniques; 3) language, clarity and graphics; 4) assignments, practice questions; 5) The possibility of accessing these textbooks.